Welsh Sojourners in India: The East India Company, Networks and Patronage, c. 1760–1840. Issue 2 (4th March 2017) - Rees, Lowri Ann
ABSTRACT: During the late eighteenth and early nineteenth centuries, within the framework of imperial expansion and exploitation there were opportunities for individuals to acquire wealth and power. Several men grew wealthy in India through the opportunities afforded to them by the East India Company, with lucrative careers and the possibility of generating money through commerce and trade. Britain witnessed the return of several East Indians, or 'nabobs' as individuals who returned home with considerable wealth were called. Indeed, some of these nabobs succeeded in amassing sizeable fortunes during their time in the East. This article aims to address a neglected area in the historiography, by examining the experiences of Welshmen as sojourners in India. In comparison with Scotland in particular, but also England and Ireland, the Welsh dimension of the East India Company is under-researched. This article highlights the existence of networks of patronage in existence in Wales which facilitated the voyage out to India and the return home of men in the employ of the East India Company during the late eighteenth and early nineteenth centuries. Networks were predominantly regional or familial, with family members supporting and sustaining loved ones during their time in India, and aiding them in their return home at the end of their sojourn in the East. The importance of letters in maintaining links with home is explored, not only as a method of relaying news, but also as a means for the sojourner to maintain an emotional link with home, and ultimately to lay the groundwork for a smooth transition home. How these Welshmen viewed themselves while out in India will be analysed, and the multi-layered nature of concepts of identity explored. Identity could be regional in focus, while some showed an awareness of a Welsh identity. Integration within the broader framework of the British East India Company is evident, as is the broader European community in the East.